Operation mechanism of organic electrochemical transistors as redox chemical transducers. Issue 36 (6th August 2021) - Tan, Siew Ting Melissa; Keene, Scott; Giovannitti, Alexander; Melianas, Armantas; Moser, Maximilian; McCulloch, Iain; Salleo, Alberto
Abstract : Designing OECTs to amplify chemical redox reactions reliably requires: (1) separating reaction from the OECT (2) operating the OECT potentiometrically (3) utilizing non-polarizable gate electrode (4) maximizing transconductance of channel material. Abstract : The ability to control the charge density of organic mixed ionic electronic conductors (OMIECs) via reactions with redox-active analytes has enabled applications as electrochemical redox sensors. Their charge density-dependent conductivity can additionally be tuned via charge injection from electrodes, for instance in organic electrochemical transistors (OECTs), where volumetric charging of the OMIEC channel enables excellent transconductance and amplification of low potentials. Recent efforts have combined the chemical detection with the transistor function of OECTs to achieve compact electrochemical sensors. However, these sensors often fall short of the expected amplification performance of OECTs. Here, we investigate the operation mechanism of various OECT architectures to deduce the design principles required to achieve reliable chemical detection and signal amplification. By utilizing a non-polarizable gate electrode and conducting the chemical reaction in a compartment separate from the OECT, the recently developed Reaction Cell OECT achieves reliable modulation of the OECT channel's charge density. This work demonstrates that systematic and rational design of OECT chemical sensors requires understanding the electrochemical processes that result in changes in the potential (charge density) of the channel, the underlying phenomenon behind amplification.